Pendidikan Bahasa Arab di Era Digital : Tantangan , Peluang dan strategi Menuju Pembelajaran Yang Efektif - Abdul Ghofur; Restu Budiansyah Riski (Program Studi Pendidikan Bahasa Arab, 2024)
The digital era has brought significant changes to various aspects of life, including education. Arabic language education has not been exempt from the influence of this era. The utilization of digital technology in Arabic language learning offers numerous new opportunities, such as broader access, more interactive learning, and personalized learning. However, the digital era also presents several challenges, such as technological access disparities, potential distractions, and the need for adaptation by teachers and students. This study aims to systematically review the literature on the development of Arabic language education in the digital era using a qualitative approach. The review will focus on the challenges, opportunities, and strategies that can be employed to maximize benefits and minimize risks in implementing digital technology in Arabic language learning. This research has several important implications, including enriching the understanding of the challenges and opportunities in Arabic language learning in the digital era, providing valuable insights for stakeholders in Arabic language education, motivating Arabic language teachers to enhance their digital skills and integrate technology into their teaching, and encouraging parents and communities to be more involved in supporting Arabic language learning in the digital era. This study has some limitations, such as not deeply investigating the effectiveness of the proposed strategies, and further research is needed to delve deeper into various aspects of Arabic language learning in the digital era. Despite these limitations, this research is expected to make a valuable contribution to the development of Arabic language education in the digital era.